Chemical Profile, Antibacterial Activity and Antibiotic-Modulating Effect of the Hexanic Zea Mays L. Silk Extract (Poaceae) - Ana Beatriz Linard de Carvalho; Cleciana Alves Cruz; Cicero Lucas Almeida de Freitas; José Junior dos Santos Aguiar; Paula Leticia Wendy de Souza Nunes; Valéria Maria da Silva Lima; Edinardo Fagner Ferreira Matias; Débora Feitosa Muniz; Henrique Douglas Melo Coutinho (MDPI AG, 2019)
The present study aimed to determine the chemical profile and to evaluate the antibacterial activity and antibiotic-modulating action of the hexanic Zea mays silk extract in association with aminoglycosides. Standard Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853 strains, as well as multi-resistant Escherichia coli 27, Staphylococcus aureus 35, and Pseudomonas aeruginosa 31 strains, were used in this study. Phytochemical prospection revealed the presence of the following secondary metabolites: tannins, flavones, flavonoids, and xanthones, with the main chemical constituents being identified in plant extracts obtained with apolar organic solvents such as hexane. The extract presented a minimum inhibitory concentration (MIC) ≥1024 μg/mL against all the tested strains. The association of the extract with aminoglycoside antibiotics showed significant synergistic effects against Staphylococcus aureus and Pseudomonas aeruginosa, except for amikacin, which was antagonized by the extract against E. coli. These results indicate the Zea mays silk presents bioactive compounds with antibiotic-modulating properties. However, further research is required to characterize the effects of isolated compounds and determine their potential for drug development.